PERUBAHAN PEDESAAN DAN FESTIVAL DI KOREA SELATAN - Seiichi, Matsumoto (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
The independence of the Republic of Korea in 1945 brought the impact of rapid infrastructure development in South Korea through a policy of increasing Foreign Investment. It also pushed the pace of modernization in rural South Korea, and also changed the face of rural culture in South Korea. The main changes perceived are demographic changes by depopulation and liberalization of agricultural imports. In addition, the traditional games of Kossa'um and traditional ceremonies also changed. Kossa'um or rope battle is currently one of the sports in the Olympics